COVID-19 / Harmeet Singh Kuldip Singh - Kuldip Singh, Harmeet Singh (Universiti Teknologi MARA, Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.